Penerapan Prinsip Lean Management dalam Meningkatkan Kinerja Industri Perkapalan : Kajian Literatur - Wahyu Alam Firdaus Syahuri; Moch. Alfin Jailani Amien; Choirul Afandi; Galih utomo; Denny Oktavina Radianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The maritime industry, as one of the vital sectors in the global economy, plays an indispensable role in facilitating international trade and the transportation of goods worldwide. However, confronted with challenges of heightened global competition and fluctuations in fuel prices, the industry needs to seek solutions to enhance efficiency and overall performance. This study assesses the application of Lean Management Principles in the maritime industry, emphasizing strategies such as value stream mapping, waste identification, and employee training as crucial for success. Findings reveal potential for enhancing operational efficiency and reducing waste, along with additional benefits such as heightened customer satisfaction and contributions to environmental sustainability. Recommendations for further research encompass case studies on Lean Management implementation in the maritime industry, the development of tailored implementation models, and investigations into the environmental ramifications of Lean Management application. In conclusion, the implementation of Lean Management holds significant promise for improving the performance of the maritime industry and fostering its overall development.